PENINGKATAN VISIBILITAS DAN PROMOSI DIGITAL KAMPUNG ADAT KURANJI - Irsyad Shabri; Rahmadianti Aulia; Yalmiadi Yalmiadi; Rahma Yanti; Widya Fhitri; Thiska Septa Maiza; Rabbi Antaridha; Emil Eka Putra; Allya Azzara Malsy Yudri; Bunga Fazilah Adelaide (Journal of Social Outreach, 2023)
Kuranji Traditional Village has the potential to become a cultural tourism object that can represent and introduce Minangkabau culture well at the national and international levels. Even so, Kuranji Traditional Village is still constrained by several crucial issues such as infrastructure, amenities and ancillary services, human resources, promotion (visibility in cyberspace), and strategic development plans. The purpose of this activity is to increase the visibility and digital promotion of the Kuranji Traditional Village in cyberspace. This activity was carried out using the workshop method; first, participants are given materials and directions; second, participants work on or practice the material that has been delivered; the three presenters and participants held discussions to resolve situational problems that were not covered in the material previously presented. The results of the activity showed positive things where managers and cultural activists in the Kuranji Traditional Village for development felt that this activity was very useful for improving the Kuranji Traditional Village as a cultural tourism object as well as an effort to increase the financial strength of the Kuranji Traditional Village community to achieve its main goal, maintenance of Minangkabau culture, through this digital promotion. Keywords: Visibility, Digital promotion, Kampung Adat Kuranji